Figurerna på guldhornetfrån Gallehus som gudomlig uppenbarelse: Ole Worms, Paul Egards, Envald Nicolaus Randulfs och Peder Winstrups tolkningsförsök - Arvidsson, Bengt (Kirkehistoriske Samlinger, 1993)
During the seventeenth century some publications of archaeological and iconographie interest about the finding of the gold horn near Gallehus in Jutland in 1639 appeared, among others by Worm, Egard, Randulf and Winstrup. The pictures of the horn were objects of a penetrating symbolic and theological interpretation. In view of the contemporary interest in Scandinavian prehistory and in collecting it was natural, for the horn to attrac archaeologic interest. But why did the pictures also awaken a theological interest? This question must be answered in the context of the contemporary theology of image. This interest is closely allied to the interest in emblems and hieroglyphs. Particularly during the seventeenth century this interest established itself in Lutheran theology and influenced the theological thinking. Worm started in his interpretation from classical authors and the Bible but also from works about hieroglyphs and emblems, e.g. Pierio Valeriano. According to Worm the pictures are an allegory of the misery and animality of human life. The pictures are admonitions to virtues and good morals. Egard’s basis of interpretation is wholly theological. According to him the pictures constitute coherent teaching on the conditions of human being in Adam and in Christ. According to Randulf the pictures symbolize and remind of points in Christian doctrine. Winstrup interprets the pictures as a political but also Christian allegory. Politically he is prophesying about conditions between Sweden and Denmark.